Training sebagai Sumber Motivasi yang dapat Meningkatkan Kinerja Karyawan - Jonner Simarmata (Universitas Batanghari, 2022)
Training does not always directly contribute to employee performance, especially in the context of small organizations. Therefore, researchers must take a mediation approach. This study aims to verify whether motivation can act as an effective mediator in the relationship between training and employee performance. For this purpose, questionnaires have been distributed to a number of Jambi batik craftsmen who were selected randomly. The collected data were analyzed by path analysis technique. The results of the analysis show that motivation has proven to be successful in being a mediator in the relationship between training and employee performance. This is because the competencies that craftsmen gain from effective training programs give them confidence so that they feel motivated in doing their jobs because the knowledge and skills match what they need. This explains that effective training not only gives employees the competencies but also the necessary work motivation. Based on these findings, small organizations such as the batik industry are recommended to design effective training programs for their artisans.